OAUNI photometry of SN2017gmr/DLT17cq - Pereyra, Antonio (2017)
Optical photometry of Type II SN2017gmr/DLT17cq (ATel #10706, ATel #10717, TNSCR 2017-1220) on 2017-09-19.207 (UT) was gathered using the OAUNI 51cm telescope at Huancayo Observatory, Peru. CCD imaging was performed in R band with seeing ~1.5" and airmass = 1.3. A total integration time of 55x20s=1100s yielded R = (14.05 +/- 0.04) mag. NOMAD field stars were used for the zero point calibration. The OAUNI project is supported by UNI, TWAS, IGP and Cienciactiva (Convenio 102-2015 Fondecyt).